Making Things Happen (Un)Expectedly: Interactive Effects of Age, Gender, and Motives on Evaluations of Proactive Behavior - Clarissa Bohlmann; Hannes Zacher (Journal of Business and Psychology, 2020)
Proactive behavior entails self-starting actions oriented toward change in the future. Other people's perceptions of an employee's proactive behavior are likely shaped by personal characteristics of the employee and related expectations. We hypothesized that the intersectionality of age, gender, and two motives (i.e., achievement and benevolence) influences others' evaluations of proactive behavior. Consistent with the social role theory and the notion of a lack of fit, results of a first experimental vignette methodology study with an employee sample (N0.167em=0.167em101; 1818 ratings) showed that proactive behavior was rated as more effective for older men compared to younger men motivated by achievement, whereas proactive behavior was rated as more effective for younger men compared to older men motivated by benevolence. Younger women compared to older women received higher effectiveness ratings for proactive behavior independent of their motive. In a second experimental vignette methodology study with a sample of participants in supervisory roles (N0.167em=0.167em164; 1205 ratings), we partially replicated the results of the first study: proactive behavior was rated as more effective for older men compared to younger men motivated by achievement, and proactive behavior was rated as more effective for younger women compared to older women motivated by achievement. In contrast, effectiveness ratings of proactive behavior of younger and older men as well as younger and older women motivated by benevolence did not differ. Overall, by investigating the intersectionality of age, gender, and motives, these findings advance research on influences of person characteristics on others' evaluations of proactive behavior.
Keywords: 650; Proactive behavior; Age; Gender; Intersectionality; Effectiveness